Brief Communication: Perinatal Transmission of Hepatitis B and Prevention Strategy - Lau, MD, MSc, MPH, Daryl T.-Y.; Holder, Sharon O. (North American Journal of Medicine and Science, 2009)
Hepatitis B is a disease of global significance. The World Health Organization (WHO) estimates that this virus currently infects 350 million people worldwide, and over three quarters of those affected are of Asian ethnicity.1 Hepatitis B is an important cause of progressive liver failure or liver cancer, complications that kill approximately 1 million people globally. In endemic regions such as Asia and Africa, HBV infection is often acquired early in life, either vertically from perinatal transmission or horizontally from contact with other infected individuals.2 In Asia, perinatal transmissions account for at least 25% of chronic hepatitis B; moreover, the transmission rates can increase to about 90% for mothers with high serum HBV DNA titers.2 Since HBeAg positive chronic hepatitis B is associated with higher levels of HBV replication, the perinatal transmission rates were as high as 80-90% among HBeAg-positive women compared to 10-20% among HBeAg-negative women.3Universal screening of all pregnant women during their pregnancy is essential to identify the ones with the highest risk of transmitting HBV to their infants.